Antibacterial Activity of Copper Nanoparticles (CuNPs) against a Resistant Calcium Hydroxide Multispecies Endodontic Biofilm - Beatriz Rojas (Nanomaterials, 2021)
Endodontic treatment reduces the amount of bacteria by using antimicrobial agents to favor healing. However, disinfecting all of the canal system is difficult due to its anatomical complexity and may result in endodontic failure. Copper nanoparticles have antimicrobial activity against diverse microorganisms, especially to resistant strains, and offer a potential alternative for disinfection during endodontic therapy. This study evaluated the antibacterial action of copper nanoparticles (CuNPs) on an ex vivo multispecies biofilm using plaque count compared to the antibacterial activity of calcium hydroxide Ca(OH)2. There were significant differences between the Ca(OH)2 and CuNPs groups as an intracanal dressing compared with the CuNPs groups as an irrigation solution (p < 0.0001). An increase in the count of the group exposed to 7 days of Ca(OH)2 was observed compared to the group exposed to Ca(OH)2 for 1 day. These findings differ from what was observed with CuNPs in the same period of time. Antibacterial activity of CuNPs was observed on a multispecies biofilm, detecting an immediate action and over-time effect, gradually reaching their highest efficacy on day 7 after application. The latter raises the possibility of the emergence of Ca(OH)2-resistant strains and supports the use of CuNPs as alternative intracanal medication.